Socio-Economic and Environmental Factors Related to Spatial Differences in Human Non-Tuberculous Mycobacterial Diseases in the Czech Republic - Modrá, Helena; Ulmann, Vít; Caha, Jan; Hübelová, Dana; Konečný, Ondřej; Svobodová, Jana; Weston, Ross Tim; Pavlík, Ivo (International journal of environmental research and public health, 2019)
Non-tuberculous mycobacteria (NTM) are ubiquitous environmental bacteria that can induce pulmonary and non-pulmonary diseases in susceptible persons. It is reported that the prevalence of NTM diseases is increasing in developed countries, but this differs by regions and countries. NTM species distribution and the rate of diseases caused by NTM vary widely in the historical territories of Moravia and Silesia (Czech Republic). This epidemiologic study of NTM diseases covers the period 2012-2018, reviews isolates obtained from patients with clinical disease and investigates correlations with related socio-economic and environmental factors. Individual NTM patients were included only once during the studied period and results were presented as incidence rate per year. The most frequently isolated NTM meeting the microbiological and clinical criteria in the study were the Mycobacterium avium-intracellulare complex, followed by Mycobacteriumkansasii and Mycobacteriumxenopi. A previously described endemic incidence of M.kansasii in the Karviná district and M.xenopi in the Ostrava district was also observed in this study. The incidence of NTM patients in the whole studied territory was 1.10/100,000 inhabitants (1.33/100,000 in men and 0.88/100,000 in women). The annual incidence of lymphadenitis in children (≤5 years of age) was 2.35/100,000 of the population of children during the 7 year period but increased in the year 2018 to 5.95/100,000. The rate of human tuberculosis in the studied area was 1.97/100,000 inhabitants. The incidence of NTM pulmonary diseases correlated with a lower socio-economic status (r = 0.63) and a higher concentration of benzo[a]pyrene pollution in the air (r = 0.64).
Keywords: Socioeconomic Factors; Male; životní prostředí; Child, Preschool; Lung Diseases; Risk Factors; Česká republika; netuberkulózní mykobakterie; Child; Environment; Nontuberculous Mycobacteria; dítě; prevalence; atypické mykobakteriální infekce; socioekonomické faktory; mužské pohlaví; incidence; Mycobacterium Infections, Nontuberculous; Czech Republic; předškolní dítě; lidé; ženské pohlaví; Humans; rizikové faktory; Prevalence; plicní nemoci; Female; lidé středního věku; Incidence; Middle Aged